2011
DOI: 10.1039/c1lc20411d
|View full text |Cite
|
Sign up to set email alerts
|

DNA manipulation with elastomeric nanostructures fabricated by soft-moulding of a FIB-patterned stamp

Abstract: A Focused Ion Beam (FIB)-patterned silicon mould is used to fabricate elastomeric nanostructures, whose cross-section can be dynamically and reversibly tuned by applying a controlled mechanical stress. Direct-write, based on FIB milling, allows the fabrication of nanostructures with a variety of different geometries, aspect ratio, spacing and distribution offering a higher flexibility compared to other nanopatterning approaches. Moreover, a simple double replication process based on poly(dimethylsiloxane) perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…Similar strategies have been used to create triangular nanochannels to stretch DNA or control its transport rate. [9][10][11][12] In the present contribution, we show that the extension of DNA in these triangular nanochannels can be mapped onto the models developed for circular and rectangular nanochannels, provided that we account for the role of the corners in a triangular channel.…”
Section: Introductionmentioning
confidence: 99%
“…Similar strategies have been used to create triangular nanochannels to stretch DNA or control its transport rate. [9][10][11][12] In the present contribution, we show that the extension of DNA in these triangular nanochannels can be mapped onto the models developed for circular and rectangular nanochannels, provided that we account for the role of the corners in a triangular channel.…”
Section: Introductionmentioning
confidence: 99%
“…Here we propose a new method that exploits the elastomeric behavior of soft polymeric materials to fabricate tuneable devices for the manipulation and trapping of DNA molecules inside a nanochannel2223. In particular, we present the fabrication process of an elastomeric Lab-On-Chip device and the characterization of the nanochannel resizing in response to a compressive strain.…”
mentioning
confidence: 99%
“…In such translocation process, the dynamical nature of the pore enable the polymer chain to translocate more efficiently as compare to the translocation of polymer in static pore [47]. On the experimental side, it has been shown that the translocation of DNA through a nanochannel can be modulated by dynamically changing the cross-section of an elastomeric nanochannel device by applying mechanical stress [48][49][50][51][52]. Time-dependent driving force are also used in the translocation process [53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%